Calcium manganese oxide catalysts for water oxidation: Unravelling the influence of various synthesis strategies. (July 2016) - Bourajoini, Hasna; Rautio, Anne-Riikka; Kordas, Krisztian; Mikkola, Jyri-Pekka
Graphical abstract: Highlights: Calcium Manganese based oxides are promising materials for water oxidation. Various synthetic routes resulted in merely different Mn oxidation states. Efficient water oxidation was observed for the obtained catalysts. Even after reutilization of hard and soft template based catalysts. Abstract: Three different mixed oxide catalysts primarily consisting of calcium and manganese oxides targeting artificial photosynthesis were synthesized and studied. According to the results, their catalytic activity for water oxidation was enhanced by the presence of mixed valence states of Mn n+ ions (3.0 ≤ n ≪ 4.0), while the specific surface area had negligible effect.